SANKSI KEBIRI DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM PIDANA INDONESIA - Ilyas, Sufyan (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This research  raises the  problem;  (1). How  is the  determination of the  sanction  of the  law that  is applied  in the Government Regulation  Substitute  Law (PERPPU)  No. 1 of 2016  according  to the  perspective of Islamic Law, (2). How  is the determination of the sanction  of the law that is stipulated  in the Government Regulation  in Lieu of Law (PERPPU)  No. 1 of 2016  according  to the perspective of Indonesian Criminal Law. This research  is a normative legal research  with normative juridical approach to trace the legal basis, be it in Islamic law or Criminal Law of Indonesia especially  related  to sanction  of kebiri, method of collecting data  using library method, after data  collected and  then analyzed  and  interpreted by using deduc- tive method that is to draw general  facts to make  facts or conclusions  gained  previously  into something  special. The results of this study conclude  that; (1). In the perspective of Islamic Law, chemical  punishment is categorized  as a punishment that has a minimum  and  maximum restriction  determined by the judge,  so it can  be classified as a ta’zir punishment. (2). According to the Indonesian Criminal Law perspective, the determination of the sanction  of kebiri aims to safeguard the welfare of the Indonesian people  from the pedophile actors,  to give a deterrent effect and  as a form of responsibility  towards  the law of the perpetrators.